2004
DOI: 10.1007/s00284-004-4288-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Virulence of Hemolysin III from Vibrio vulnificus

Abstract: Vibrio vulnificus, a highly virulent marine bacterium, is the causative agent of both serious wound infections and fatal septicemia in many areas of the word. A gene (hlyIII) encoding a hemolysin was cloned and sequenced from V. vulnificus. Nucleotide sequence analysis predicted an open reading frame of 642 bp encoding a 214 amino acid polypeptide that showed 48% sequence identity to the hemolysin III of Bacillus cereus. When HlyIII of V. vulnificus was expressed in Escherichia coli, crude extracts exhibited h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 27 publications
0
43
0
1
Order By: Relevance
“…TMX is a conserved, single-domain protein of unknown function that is homologous to a hemolysin III-related (HlyIII) protein in Bacillus cereus (26,27). Some evidence, obtained using recombinantly expressed HlyIII proteins in the heterologous E. coli background, suggested that HlyIII-related proteins function as hemolysins (28), but their presence in all bacteria makes this hypothesis unlikely. The function of HlyIII proteins has not been conclusively determined (29), but they were shown to be distant homologs of adipoR receptors found in yeasts and humans (29), the function of which also remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…TMX is a conserved, single-domain protein of unknown function that is homologous to a hemolysin III-related (HlyIII) protein in Bacillus cereus (26,27). Some evidence, obtained using recombinantly expressed HlyIII proteins in the heterologous E. coli background, suggested that HlyIII-related proteins function as hemolysins (28), but their presence in all bacteria makes this hypothesis unlikely. The function of HlyIII proteins has not been conclusively determined (29), but they were shown to be distant homologs of adipoR receptors found in yeasts and humans (29), the function of which also remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…The type III hemolysin, a virulence factor in numerous pathogenesis, is an integral outer membrane protein with hemolytic activity. 100,101 Lipopolysaccarides (LPS) is an outer membrane virulence factor of C. sakazakii, which interacts with enterocytes through LPS mediated binding to TLR4 inducing NEC in animals. [102][103][104][105] In the NEC patients, the elevated level of LPS in serum and stools has been reported.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…P. falciparum hemolysin III (PfHly III) is located on chromosome 14. Homologues have been identified in all Plasmodium genomes sequenced, including P. vivax, P. yoelii, P. berghei, and P. knowlesi, as well as Toxoplasma and Babesia genomes.…”
mentioning
confidence: 99%
“…Mass spectrometry detected PfHly III in gametocytes (11). From Bacillus cereus and Vibrio vulnificus Hly III studies, Hly III was shown to be a pore-forming protein, 3 to 3.5 nm in diameter, with optimal hemolysis at 37°C (12)(13)(14). Over evolutionary time, hemolysins have adapted essential transport roles in Plasmodium, contrasting with their ancient bacterial pore-forming cytotoxic effect.…”
mentioning
confidence: 99%